English phonetics and phonology: A practical course - Roach, Peter (New York : Cambridge University Press, 2000)
Este es un curso básico completo en Inglés fonética y fonología. Desde su publicación se ha establecido a sí misma como la forma más práctica, completa en el campo de texto y se utiliza ampliamente en muchas universidades y otras Instituciones de educación superior. La utiliza tanto nativos y no nativos, que pueden ser de formación superior que enseñan o estudian la lengua a nivel avanzado
Preface to the third edition -- List of symbols -- Chart of the international phonetic alphabet -- How to use this book -- 1. Introduction -- 2. The production of speech sounds -- 3. Long vowels, diphthongs triphthongs -- 4. Voicing and consonants -- 5. The phoneme -- 6.Fricatives and affricates -- 7. Nasals and other consonants -- 8. The syllable -- 9. Strong and weak syllables -- 10. Stress in simple words -- 11. Complex word stress -- 12. Weak forms -- 13. Problems in phonemic analysis -- 14. Aspects of connected speech -- 15-17. Intonation -- 18 y 19. Funtions of intonation -- 20.Further areas of study in phonetics and phonology.
Contiene bibliografía. (p.273-279)
Keywords: Inglés -- Fonética; Inglés -- Fonología